Application of Passive Integrated Transponder Technology to Juvenile Salmon Habitat Use on an Experimental Agricultural Floodplain. (2nd January 2016) - Conrad, J. Louise; Holmes, Eric; Jeffres, Carson; Takata, Lynn; Ikemiyagi, Naoaki; Katz, Jacob; Sommer, Ted
Abstract: Passive integrated transponder (PIT) technology allows passive, individual identification of small fish, making it a potentially useful tool to address an information gap of juvenile salmon habitat use in off-channel environments. We investigated the combined use of field enclosures and PIT technology as a method for studying the habitat preference of juvenile Chinook Salmon Oncorhynchus tshawytscha on a flooded rice field, a potential surrogate for lost floodplain habitat. We stocked two field enclosures (182 m 2 ) with 42 juvenile salmon. One enclosure had equal portions of rice stubble, disced, and fallow habitat treatments, and the second contained only the disced treatment. Fish were tagged with 8- or 12-mm-sized PIT tags, and generated approximately 1 million detections in each enclosure over 14 d. We used a condensing procedure to reduce the data volume while preserving habitat use patterns. The smaller 8-mm tags were only detected along antenna edges, and the 12-mm tags had broader but more variable detection fields. Despite this difference, habitat occupancy probabilities showed the same spatial pattern between tag sizes, with increased occupancy in the upstream locations of both field enclosures. Similar results between tag sizes suggest that valuable habitat use data can be obtained with the 8-mm tag. Received January 30, 2015; accepted October 13, 2015